2021
DOI: 10.3390/nano11030823
|View full text |Cite
|
Sign up to set email alerts
|

Sulvanites: The Promise at the Nanoscale

Abstract: The class of ternary copper chalcogenides Cu3MX4 (M = V, Nb, Ta; X = S, Se, Te), also known as the sulvanite family, has attracted attention in the past decade as featuring promising materials for optoelectronic devices, including solar photovoltaics. Experimental and theoretical studies of these semiconductors have provided much insight into their properties, both in bulk and at the nanoscale. The recent realization of sulvanites at the nanoscale opens new avenues for the compounds toward printable electronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 62 publications
(157 reference statements)
0
11
0
Order By: Relevance
“…[77] Recently, Wu et al have revealed a similar phenomenon for Cu 3 VS 4 NCs, where the QYs increased from 1% to 10% with a long radiative lifetime after adding a CdS shell. [78,79] Like other I-III-VI 2 semiconductor NCs, CuFeS 2 based core/ shell NCs also show long defect-mediated emission kinetics. Regardless of the shell (CdS or ZnS), CuFeS 2 based-core shell NCs have lifetimes on the microsecond time scale.…”
Section: Luminescencementioning
confidence: 99%
See 1 more Smart Citation
“…[77] Recently, Wu et al have revealed a similar phenomenon for Cu 3 VS 4 NCs, where the QYs increased from 1% to 10% with a long radiative lifetime after adding a CdS shell. [78,79] Like other I-III-VI 2 semiconductor NCs, CuFeS 2 based core/ shell NCs also show long defect-mediated emission kinetics. Regardless of the shell (CdS or ZnS), CuFeS 2 based-core shell NCs have lifetimes on the microsecond time scale.…”
Section: Luminescencementioning
confidence: 99%
“…have revealed a similar phenomenon for Cu 3 VS 4 NCs, where the QYs increased from 1% to 10% with a long radiative lifetime after adding a CdS shell. [ 78,79 ]…”
Section: Optical Propertiesmentioning
confidence: 99%
“…While the ternary (AE)M 4+ Q 3 materials, and other examples of ternary materials in this class such as the sulvanites (Cu 3 M 0 S 4 , M 0 = V, Nb, Ta), are of interest because of their potential optoelectronic applications including in solar cells, many of the binary materials boast layered structures that make them of interest for battery materials, and many also may have (photo)catalytic applications. [5][6][7][8][9][10][11][12][13] While the preparation of phase-pure ternary materials presents special challenges given the need to balance the reactivity of different metal precursors, important lessons can be learned from understanding the synthetic pathways and approaches to the related binary materials. The goal of this feature article, therefore, is to interrogate this area to develop an understanding of the current state-of-the-art of early transition metal chalcogenide nanomaterial synthesis, including both ternary and binary materials.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, sulvanite-type Cu 3 MX 4 (M = V, Nb, and Ta; X = S, Se, and Te) compounds have been regarded as promising photoabsorbers for the conversion of solar energy into electricity and fuels due to their extraordinary properties, including tunable bandgap energy, high optical absorption coefficient, and readily available and comparatively abundant elements. [22][23][24][25][26][27][28][29] For example, Ikeda et al reported that Cu 3 Nb 1−x V x S 4 shows promise for application in photocatalytic H 2 evolution under visible light irradiation. 30 Liu et al reported that Cu 3 VS 4 nanocrystals can be tuned from plasmonic-like to excitonic simply via coating with CdS shells.…”
Section: Introductionmentioning
confidence: 99%